Unveiling the hidden role of extracellular vesicles in brain metastases: a comprehensive review - Li, Ji; Lu, Shuangqing; Chen, Feihu; Zhu, Hui (Frontiers in Immunology, 2024)
Background Extracellular vesicles (EVs) are small, transparent vesicles that can be found in various biological fluids and are derived from the amplification of cell membranes. Recent studies have increasingly demonstrated that EVs play a crucial regulatory role in tumorigenesis and development, including the progression of metastatic tumors in distant organs. Brain metastases (BMs) are highly prevalent in patients with lung cancer, breast cancer, and melanoma, and patients often experience serious complications and are often associated with a poor prognosis. The immune microenvironment of brain metastases was different from that of the primary tumor. Nevertheless, the existing review on the role and therapeutic potential of EVs in immune microenvironment of BMs is relatively limited. Main body This review provides a comprehensive analysis of the published research literature, summarizing the vital role of EVs in BMs. Studies have demonstrated that EVs participate in the regulation of the BMs immune microenvironment, exemplified by their ability to modify the permeability of the blood-brain barrier, change immune cell infiltration, and activate associated cells for promoting tumor cell survival and proliferation. Furthermore, EVs have the potential to serve as biomarkers for disease surveillance and prediction of BMs. Conclusion Overall, EVs play a key role in the regulation of the immune microenvironment of brain metastasis and are expected to make advances in immunotherapy and disease diagnosis. Future studies will help reveal the specific mechanisms of EVs in brain metastases and use them as new therapeutic strategies.